Effect of chromium on microstructure and toughness of intercritical heat affected zone of low carbon steel - Eroglu, M; Aksoy, M; Khan, TI (Maney Publishing, 2002)
In the present study, the effect of chromium along with varying cooling rate on the microstructure and toughness of the intercritical heat affected zone (HAZ) of a low carbon steel was investigated using the weld thermal simulation technique. In the thermal simulation experiments, low carbon steel specimens containing five different chromium contents, 0.44, 0.92, 1.4, 1.82, and 2.3 wt-% were studied. The induction heated specimens were cooled at various rates, to represent bead on plate welds made on a 12.5 mm thickness plate with heat inputs of 0.5, 1, and 2 U mm(-1). Following thermal simulation, the microstructure, hardness, and toughness of the intercritical HAZ were investigated. From the results, attempts were made to establish a relationship between cooling time from 600 to 400degreesC, chromium content, microstructure, hardness, and toughness. From Charpy impact test results and microstructural observations, it was seen that a chromium content of 0.92 wt-% or greater and the shortest cooling time were effective in forming the brittle phases, martensite and bainite, thereby producing lower toughness. However, longer cooling times were effective in the formation of ductile phases, ferrite and pearlite, thereby giving higher toughness values. It was concluded that, taking into consideration, the microstructure, hardness, and toughness of the intercritical HAZ, the longest cooling time simulating the highest heat input gave good results for all chromium contents. However, it was also seen that satisfactory toughness values could be obtained with shorter cooling times when the chromium content was under 1.82 wt-%.